THE INFLUENCE OF INTEGRITY, COMPETENCE, ORGANIZATIONAL COMMUNICATION, AND WORK ENVIRONTMENT ON EMPLOYEE PERFORMANCE THROUGH WORK MOTIVATION AND ORGANIZATIONAL COMMITMENT - Ragil, Bambang; Hadiyati, Ernani; Suswati, Endang; Mulyono, Sugeng; Gunadi, Gunadi (Jurnal Manajemen Terapan dan Keuangan, 2025)
This study aims to analyze the effects of integrity, competence, organizational communication, and work environment on employee performance, with work motivation and organizational commitment as mediating variables, in Islamic banks in Malang City, East Java. A quantitative explanatory research approach was employed. Data were collected through structured questionnaires administered to 150 employees of an Islamic bank, selected using purposive sampling. Data analysis was conducted using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The results indicate that competence and organizational communication have positive and significant effects on employee performance, while integrity and work environment do not have a significant direct effect on performance. However, all four variables—integrity, competence, organizational communication, and work environment—have positive and significant effects on work motivation and organizational commitment. Work motivation and organizational commitment are also proven to have positive and significant effects on employee performance. Mediation analysis reveals that work motivation and organizational commitment fully mediate the effects of integrity and work environment on employee performance, and partially mediate the effects of competence and organizational communication on performance. These findings emphasize that improving employee performance in Islamic banks depends not only on technical competence and effective communication, but also on the organization’s ability to foster integrity, create a supportive work environment, and systematically manage employee motivation and commitment